Indonesian pre-service teachers’ mindfulness, social emotional competence, and academic achievement - Pudja Hermana; Zuraida Zuraida; Lingga Agustina Suganda (International Journal of Evaluation and Research in Education (IJERE), 2021)
Pre-service teachers must be able to fulfill the standards of having teachers’ competencies and more than adequate knowledge to teach the future generations. In relation to this, mindfulness, social emotional competence, and academic ability become crucial reasons they need in perceiving the quality to become professional teachers. The respondents of this study were 68 students who were English as a Foreign Language (EFL) pre-service teachers ranging from the age of 19-22 from the Faculty of Teacher Training and Education at one of the university in South Sumatra, Indonesia. The aims of this study were to find out the relationship among these pre-service teachers’ mindfulness, social emotional competence and academic achievement. The instruments of this study were the five-facet mindfulness and social emotional competence questionnaires. The documentation of their GPA which were analyzed using Pearson Product Moment Test. The results of this study showed that pre-service teachers had high level of mindfulness and social emotional competence. It also highlighted that there were significant weak correlation between their five facet mindfulness and academic achievement, and their five facet mindfulness and social emotional competence toward academic achievement. Specifically, the non-judging dimension from the five-facet mindfulness and self-management from social emotional competence also correlated significantly to academic achievements. In conclusion, the pre-service teachers’ mindfulness, social emotional competence, and academic achievement had beneficial relationship one another.